Homeostatic Eosinophils: Characteristics and Functions - Marichal, Thomas; Mesnil, Claire; Bureau, Fabrice (Frontiers in Medicine, 2017)
Eosinophils are typically considered to be specialized effector cells that are recruited to the tissues as a result of T helper type 2 (Th2) cell responses associated with helminth infections or allergic diseases such as asthma. Once at the site of injury, eosinophils release their cytotoxic granule proteins as well as preformed cytokines and lipid mediators, contributing to parasite destruction but also to exacerbation of inflammation and tissue damage. Accumulating evidence indicates that, besides their roles in Th2 responses, eosinophils also regulate homeostatic processes at steady state, thereby challenging the exclusive paradigm of the eosinophil as a destructive and inflammatory cell. Indeed, under baseline conditions, eosinophils rapidly leave the bloodstream to enter tissues, mainly the gastrointestinal tract, lungs, adipose tissue, thymus, uterus and mammary glands, where they regulate a variety of important biological functions, such as immunoregulation, control of glucose homeostasis, protection against obesity, regulation of mammary gland development, and preparation of the uterus for pregnancy. This article provides an overview of the characteristics and functions of these homeostatic eosinophils.